Lung Perfusion Scintigraphy Early After COVID-19: A Single-Center Retrospective Study - Sajal, De; Mudalsha, Ravina; Tinu, Lukose; Ranganath, T. Ganga; Dibakar, Sahu (Journal of nuclear medicine technology, 2021)
The incidence of thromboembolic complications in coronavirus disease 2019 (COVID-19) infection is well recognized. The present study retrospectively evaluated the type and prevalence of lung perfusion defects in early-post-COVID-19 patients with hypoxia and was aimed to identify the risk factors for mismatched perfusion defects. We analyzed SPECT/CT images of 54 early-post-COVID-19 patients (44 men and 10 women). Logistic regression analysis was used to examine the risk. The mean age of the study population was 55.4 y (range, 34-76 y). All received prophylactic anticoagulation from the day of hospitalization to the date of perfusion scanning. The median interval between COVID-19-positive reports and lung perfusion scanning was 22 d. Lung perfusion defects (of any type) were observed in most (87%). Twenty-three subjects (42.6%) had mismatched perfusion defects. Mismatched perfusion defects were segmental in 14 subjects (25.9%) and subsegmental in 11 (20.4%). Higher age was a risk factor for mismatched perfusion defects (odds ratio, 1.06; 95% CI, 0.99-1.13; = 0.06). Subjects with a serum D-dimer level of at least 2,500 ng/mL on the day before the scan were not at higher risk for having mismatched perfusion defects (odds ratio, 1.14; 95% CI, 0.34-3.9; = 0.83). Despite prophylactic anticoagulation, mismatched perfusion defects suggestive of pulmonary thromboembolism were observed. Serum D-dimer level in patients early after COVID-19 is a poor predictor of mismatched perfusion defects. Confirmed evidence of pulmonary embolism by imaging studies should support the decision to extend anticoagulant prophylaxis in post-COVID-19 patients.